Evolutionary Adaptation of Protein Turnover in White Muscle of Stenothermal Antarctic Fish: Elevated Cold Compensation at Reduced Thermal Responsiveness - Nina Krebs; Christian Bock; Jan Tebben; Felix C. Mark; Magnus Lucassen; Gisela Lannig; Hans-Otto Pörtner (Biomolecules, 2023)
Protein turnover is highly energy consuming and overall relates to an organism’s growth performance varying largely between species, e.g., due to pre-adaptation to environmental characteristics such as temperature. Here, we determined protein synthesis rates and capacity of protein degradation in white muscle of the cold stenothermal Antarctic eelpout (Pachycara brachycephalum) and its closely related temperate counterpart, the eurythermal common eelpout (Zoarces viviparus). Both species were exposed to acute warming (P. brachycephalum, 0 °C + 2 °C day−1; Z. viviparus, 4 °C + 3 °C day−1). The in vivo protein synthesis rate (Ks) was monitored after injection of 13C-phenylalanine, and protein degradation capacity was quantified by measuring the activity of cathepsin D in vitro. Untargeted metabolic profiling by nuclear magnetic resonance (NMR) spectroscopy was used to identify the metabolic processes involved. Independent of temperature, the protein synthesis rate was higher in P. brachycephalum (Ks = 0.38–0.614 % day−1) than in Z. viviparus (Ks= 0.148–0.379% day−1). Whereas protein synthesis remained unaffected by temperature in the Antarctic species, protein synthesis in Z. viviparus increased to near the thermal optimum (16 °C) and tended to fall at higher temperatures. Most strikingly, capacities for protein degradation were about ten times higher in the Antarctic compared to the temperate species. These differences are mirrored in the metabolic profiles, with significantly higher levels of complex and essential amino acids in the free cytosolic pool of the Antarctic congener. Together, the results clearly indicate a highly cold-compensated protein turnover in the Antarctic eelpout compared to its temperate confamilial. Constant versus variable environments are mirrored in rigid versus plastic functional responses of the protein synthesis machinery.